Some Scholarly Considerations on the Study of Faqiriy’s Life and Literary Legacy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
During the reign of Muhammad Rahimkhan II Feruz, science, art, culture, and literature in Khorezm experienced significant development and reached a remarkable peak. Among the gifted poets of the literary environment of that era was Abdurazzoq Abdujabbor oghli Faqiriy. This article presents information related to the study of the poet’s life and creative legacy. It outlines the research conducted thus far on his biography and literary heritage, as well as the main directions of these studies. The scholarly works on Faqiriy’s poetry can be broadly divided into two categories. The first includes general studies of the literature of that period, in which his poetry is analyzed in a broader context. The second consists of specialized research focused directly on his literary works.